Rutile from the crystalline rocks of the southwestern part of the Ukrainian shield - PAVLIUK, Oleksandra; PAVLIUK, Viacheslav; SEMENIV, Oleh (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. Rutile is a widespread accessory mineral in crystalline rocks of the Ukrainian Shield, notable for its geochemical stability and capacity to incorporate trace elements like Nb, Fe, V, Zr, Al and a wide range of other trace elements. The aim of this study is to analyze the color, morphology, and chemical composition of rutile from indigenous crystalline rocks of the southwestern part of the Ukrainian Shield in order to identify diagnostic features characteristic of different rock types, as well as to enable stratigraphic reconstructions and track the migration of sedimentary rutile. Methods, Samples and Analytical details. The study is based on the analysis of 363 rutile crystals extracted from 57 heavy mineral concentrate samples, as well as textual archival materials from 11 geological surveys conducted by the Right-Bank Geological Expedition between 1972 and 2009. The samples represent rutile from various lithotypes, including granites, gneisses, pegmatites, enderbites, ultrabasic rocks, and other crystalline formations of the southwestern part of the Ukrainian Shield. Binocular microscopy and SEM-EDS analysis were used to examine rutile morphology and chemical composition. Results. Rutile content ranges from 0.8 g/t in enderbites to 109.4 g/t in sillimanite-biotite gneisses. Most crystals are black or dark brown and acicular in form, often included in quartz or biotite. The majority (72 %) of rutile samples contain trace impurities, with V, Nb, Cr, and Fe being most common. Impurity patterns vary with rock type, metamorphic grade, and regional distribution. Northern rocks (e.g., Fastiv area) show Nb–V–Fe associations; southern samples often contain isolated V. Chromium-bearing rutile was discovered in migmatized metabasites in the Berdychiv area. Conclusions. Rutile preserves the geochemical signature of its host rocks and reflects both lithological and metamorphic conditions. It can serve as a reliable indicator mineral for reconstructing the provenance of sedimentary rutile, and Nb–Cr trace element associations may assist in identifying potentially diamond-bearing source rocks.
Keywords: Rutile; southwestern part of the Ukrainian Shield; crystalline rocks; chemical composition